Assessing the association of ESR1 polymorphisms with male infertility in Vietnamese population - Quy Vu, Phan; Huu Dinh, Tran; Thuy Duong, Nguyen (Vietnam Journal of Biotechnology, 2023)
Male infertility is a prevalent global concern, impacting an estimated 7% of the male population. Many single nucleotide polymorphisms (SNPs) linked to idiopathic male infertility have been discovered since the 1990s, including two intronic SNPs of the estrogen receptor α gene (ESR1), namely rs9340799 and rs2234693. However, the associations of the two SNPs with male infertility have yielded inconsistent results across different populations. In this study, we aimed to assess the association of ESR1 rs9340799 and ESR1 rs2234693 with male infertility in a cohort of Vietnamese individuals consisting of 154 fertile men and 146 infertile men. Genotyping ESR1 rs9340799 and ESR1 rs2234693 for 300 samples was performed using polymerase chain reaction-restriction fragment length polymorphism (PCR - RFLP). The frequencies of genotypes and alleles were analyzed using bioinformatic tools. The genotype distributions of ESR1 rs9340799 and ESR1 rs2234693 followed Hardy-Weinberg equilibrium, but no association of the two SNPs with male infertility was established (p > 0.05) in the additive, dominant, recessive, and allele models. Notably, the haplotype analysis revealed a strong association between the haplotype GT and a decreased risk of male infertility (OR = 0.226; 95% CI = 0.106 - 0.484; p < 0.001). The findings provide additional knowledge about the roles of single nucleotide polymorphisms in male infertility in the Vietnamese population.